Formation of the measuring channel for quantum diagnostic computer - S. V. Dianov; V. M. Novichkov (Научный вестник МГТУ ГА, 2019)
Modem and perspective tasks of robotics with control from artificial intelligence systems require the use of small-sized measuring devices. In this case, the intensively developed quantum sensors and quantum computers have good prospects. Their main advantage is the ability to successfully process the data of random processes with decomposition of complex functions into simple multipliers, as well as their small size and the ability to transmit data over long distances without wires. Data transmitted over quantum communication lines cannot be copied or intercepted, which is very useful for remote control of complex technical systems. Based on the results of the probabilistic noisy data analysis quantum computer can quickly develop an assessment of the complex system technical condition. At the same time, there is no need to go through all the possible solutions to the evaluation problem with a huge amount of input data, some of which can sometimes be undefined. The main problem in the research of quantum processes is that researchers study the processes occurring in materials, but they do not indicate the ways in which quantum sensors and quantum computers are used in practical applications. This article explains how to form a measurement channel that will be compatible with a quantum computer, how to organize the input of information about the measured physical quantity into a quantum computer using a quantum sensor. The main objective was to bring the results of basic research in the field of quantum computing closer to their application in applied tasks. It is shown how the quantum processes can be shifted to the field of physical quantities technical measurements used in the automatic diagnosis of the technical state of complex systems. In the process of obtaining the results of the study, the deduction method of conclusions within the framework of a systematic approach to the development of technical systems elements was used. The result is a description of the processes in the quantum measuring channel, which is used to enter diagnostic data in a quantum computer. The study main conclusions breed the idea that quantum sensors implemented in the form of a modified diamond crystal are well described by the theory of measuring transducers with frequency output and can be used in diagnostic computers.